2012
DOI: 10.1093/jac/dkr558
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome among HIV-infected Taiwanese patients in the era of highly active antiretroviral therapy: prevalence and associated factors

Abstract: Approximately one-fourth of HIV-infected Taiwanese patients developed metabolic syndrome in the HAART era. Receipt of HAART and prolonged exposure to PI and nucleoside reverse transcriptase inhibitor(s) were associated with metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
2
21

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 46 publications
3
34
2
21
Order By: Relevance
“…Jantarapakde et al (19) reported a higher prevalence of lipodystrophy and median total cholesterol, HDL-cholesterol, and triglycerides in patients who had received antiretroviral therapy. Moreover, increases in mean total cholesterol, HDL-cholesterol, and triglyceride levels were observed as the duration of antiretroviral therapy increased in previous studies in Asian patients (2021). Therefore, in consideration of these studies, it can be presumed that antiretroviral therapy influenced the prevalence of metabolic complications.…”
Section: Discussionmentioning
confidence: 58%
“…Jantarapakde et al (19) reported a higher prevalence of lipodystrophy and median total cholesterol, HDL-cholesterol, and triglycerides in patients who had received antiretroviral therapy. Moreover, increases in mean total cholesterol, HDL-cholesterol, and triglyceride levels were observed as the duration of antiretroviral therapy increased in previous studies in Asian patients (2021). Therefore, in consideration of these studies, it can be presumed that antiretroviral therapy influenced the prevalence of metabolic complications.…”
Section: Discussionmentioning
confidence: 58%
“…Third, we did not have an HIV-uninfected population for comparison in terms of the frequency of comorbidity. Therefore, it is not known whether the frequency of any comorbidity examined in this study is higher in HIV-infected patients than in HIV-uninfected patients in Taiwan, although several studies have suggested that cART and HIV infection may accelerate aging and increase risk of metabolic, cardiovascular and renal complications [10], [14], [15], [39], [40], [42].…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have provided evidence that comorbidities such as diabetes mellitus [6][11], hypertension [6], [8], [9], [12], coronary artery disease [11], hyperlipidemia [13], [14], renal disease [7], [11], [15], and reduced bone mineral density [16][18] are more common among HIV-infected elderly patients than HIV-uninfected controls. Other than cART, medications for management of metabolic complications and cardiovascular diseases will be needed, which will increase the pill burden and potential for drug-drug interactions in the elderly patients [19],[20].…”
Section: Introductionmentioning
confidence: 99%
“…Some retrospective studies have found a higher prevalence of MS associated with exposure to HAART [13,18,31,39] and in particular with older PIs [14,18,19,31,34,36,38,39,42,51,99] and thymidine analogues [14,19,33,42], however this has not been confirmed in other studies [12,15,16,20,25,27,29]. …”
Section: The Role Of Antiretroviral Therapy In the Metabolic Syndromementioning
confidence: 99%